ELECTRONIC GOVERNMENT IN THE RUSSIAN FEDERATION EXECUTIVE BODIES OF THE CONSTITUENT ENTITIES - Irina Novikova; Slavko Rudich (Вестник Северо-Кавказского федерального университета)
T present the organization model of «e-government» in the Russian Federation and its regions is inefficient and requires a specific institutional modification of the interdepartmental cooperation mechanisms. There is a clear need for a common base of regulation, for example, a systematic set of legislative provisions, in the form of electronic code of statehood, which should be a set of norms and rules specifying relations in the area of «e-government» subjects of the Russian Federation and the activities of their Executive bodies using the pn nciples of e-state.